Configuration Design for the Spatial 3-DOF Translation Fully Compliant Parallel Mechanism - Li Kunquan; Wen Rui (Jixie chuandong)
The compliant hinge of fully compliant parallel mechanism has the defects of creep deformation,backhaul reaction and stress relaxation,two different configurations of fully compliant parallel mechanism are designed based on the spatial parallel mechanism prototype. Firstly,based on hinge replacement method,one kind of fully compliant parallel mechanism is established. Secondly,one kind of integrated fully compliant parallel mechanism is designed by adopting type synthesis and topology optimization method. Finally,the model of static stiffness analysis and modal analysis are established,then the simulation analysis and experiment test are carried out correspondingly. The results show that compared with the first scheme fully compliant parallel mechanism,the integrated fully compliant parallel mechanism has higher motion accuracy,better stiffness characteristics and vibration resistance,the effectiveness of topology optimization design method for integrated fully compliant parallel mechanism is verified.